On the variation of kinetic energy in a hydraulic inertial motion converter - Yu. A. Burian; G. S. Russkikh (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The research investigates the dynamics of a hydraulic inertial motion converter in a non-conservative system. The hydraulic inertial motion converter portion of the inertial tubes in the piston is overlapped synchronously with the change in direction of piston velocity. The cylinder piston is forced into progressive oscillating motion by a servo drive, which is mounted on a movable platform along with the cylinder. The relative movement of the cylinder piston in a non-conservative system leads to an increase in kinetic energy, which could affect the motion of the moving platform, both in the absence of resistance forces and when the resistance is small and proportional to the platform velocity.